A new species of eriophyid mite from Iran (Acari: Prostigmata: Eriophyidae) - Flechtmann, Carlos H.w.; Tarasi, Javad; Saboori, Alireza (Zootaxa, 2003)
A survey conducted on cultivated black poplar, Populus nigra (L.) Black. (Salicaceae) in Iran led to the discovery of a new species of eriophyid mite, Aceria zanjani n. sp. from Zanjan, Northwest of Iran.